Safety and feasibility of laparoscopic and endoscopic cooperative surgery for duodenal neoplasm: a retrospective multicenter study - Nunobe, Souya; Ri, Motonari; Yamazaki, Kimiyasu; Uraoka, Masanao; Ohata, Ken; Kitazono, Iwao; Terashima, Masanori; Yamagata, Yukinori; Tanabe, Satoshi; Abe, Nobutsugu; Tsuji, Toshikatsu; Niimi, Keiko; Kawakubo, Hirofumi; Tsukada, Tomoya; Kitashiro, Shuji; Ishizuka, Naoki; Hiki, Naoki; Society for the Study of Laparoscopic Endoscopic Cooperative Surgery (Endoscopy, 2021)
Background A delayed perforation can often occur after endoscopic treatment for duodenal neoplasms and may be fatal due to leakage of pancreatic and bile juices. We aimed to evaluate the feasibility and safety of laparoscopic and endoscopic cooperative surgery for duodenal neoplasms (D-LECS) in a multicenter, retrospective study.Methods The clinical characteristics and surgical outcomes of 206 patients with duodenal neoplasms in whom D-LECS had initially been attempted at one of 14 institutions were reviewed retrospectively. Results Of the 206 patients, 63 (30.6 %), 128 (62.1 %), and 15 patients (7.3 %) had lesions at the bulb, second portion, and third portion of the duodenum, respectively. The rates of en bloc and R0 resections during D-LECS were 96.1 % and 95.1 %, respectively. Intraoperative and delayed perforations occurred in 10 (4.9 %) and 5 patients (2.4 %), respectively. No cases of recurrence were observed. Surgical duration of ≥ 180 minutes was an independent risk factor for postoperative complications.Conclusions The results revealed that D-LECS was performed with oncological safety and technical feasibility.